Clubes sociais negros: lugares de memória, resistência negra, patrimônio e potencial - Escobar, Giane Vargas (2010)
The Black Social Clubs had an important place in Brazilian society formation. They broke the standards of a time, acting in the fight against slavery and the racial discrimination. The more ancient place is located in Rio Grande do Sul (South of Brazil), and it represents the greater representation. The objective of this study is to know what principal measures should be done by the club managers and State about the preservation of these places that, in the end of the XX century and the beginning of the new millennium, have been searching survive to the disarticulating problems, neglecting and asking for help. The methodology of this work is a documentary and bibliographic research as well as techniques of the oral history and participant observation, with econographic character, doing an analysis of the final routings of the 1st National Meeting of Black Clubs and Societies, occurred in 2006, in Santa Maria/RS. This meeting was a historical mark, constructing a new paradigm with demands registered in the Santa Maria Letter , which pointed the principal guidelines for the club directors and the Public Power in coming years. The investigation has the principal objective of suggesting public policies in order to preserve, keep, strengthen, spread and safeguard these places of resistance and black identity, focusing the study on Treze de Maio, a Black Social Club created by workers of the extinct railroad in Santa Maria, RS, Brazil, mainly in its birth, from 1903 to 1914 and its revitalization as a community museum in the XXI century. This museum appears as a strategy, a reinvention of the heritage, with an eye in the past, searching the origins, but with actions in the present to recognize and register this centennial club and other pairs as immaterial heritage of Brazilian society. In this sense, it is consider as the principal result of this work, the opening process of the Social Black Clubs Register in Brazil, by the National Historic and Heritage Institute, (NHHI) in November 5th,2009, which will guarantee, after the inventory, the elaboration of a Safeguard Plan, which contemplates the National Politic of Immaterial Heritage.